2019
DOI: 10.1002/14651858.cd012449.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and experiences of labour companionship: a qualitative evidence synthesis

Abstract: BackgroundLabour companionship refers to support provided to a woman during labour and childbirth, and may be provided by a partner, family member, friend, doula or healthcare professional. A Cochrane systematic review of interventions by Bohren and colleagues, concluded that having a labour companion improves outcomes for women and babies. The presence of a labour companion is therefore regarded as an important aspect of improving quality of care during labour and childbirth; however implementation of the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
208
0
24

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(244 citation statements)
references
References 147 publications
(908 reference statements)
12
208
0
24
Order By: Relevance
“…Allowing birth companions during labor and delivery is highly recommended by WHO [40]. Our study con rmed the positive in uence of birth companions for both the midwife and laboring women.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Allowing birth companions during labor and delivery is highly recommended by WHO [40]. Our study con rmed the positive in uence of birth companions for both the midwife and laboring women.…”
Section: Discussionsupporting
confidence: 73%
“…They don't show respect anymore." (Midwife FGD 1, age group [31][32][33][34][35][36][37][38][39][40] Underappreciated within the hospital Midwives felt their work and efforts were not always appreciated within the hospital, especially compared to the appreciation and privileges that doctors received.…”
Section: Resultsmentioning
confidence: 99%
“…Labor is perhaps the area that generates the most uncertainty and anxiety during pregnancy, especially for first-time mothers: specific posts in our sample included questions about how to discern when one is in labor and/or when one's water has broken; when to go the hospital; how to induce labor; and how to cope when a birth is proceeding differently than expected. Given the significant informational and support needs related to labor, it is not surprising that studies have consistently found benefits of companionship during the labor process (e.g., such as that provided by a doula) [39][40][41]. The results of our study, which indicate that there is still a significant unmet informational and emotional support need, support ACOG's recommendation of incorporating support personnel such as doulas during labor, as well as other suggestions to have labor support routinely provided by healthcare systems [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Critical reflection on the physical design and organization of maternity services, for example by using humancentered design approaches, may be a valuable approach to ensure that services are useful, desirable, and usable to the woman and her family, while ensuring efficiency and effectiveness to the provider [32] . Using human-centered design approaches may also be a useful tool to implement effective interventions, including continuous support for women during labor and childbirth [33], particularly where there may be resistance from providers [34]. Continuous support has been demonstrated to improve women's experiences of childbirth [33], particularly related to improving communication, emotional support and respect and dignity.…”
Section: Discussionmentioning
confidence: 99%